Pengaruh Media Komik Sahabat Anak Muslim Dalam Peningkatan Motivasi Belajar Peserta Didik Mata Pelajaran Pendidikan Agama Islam Di SDN Gondang - Istiqomah; Rofiq, Muhammad Husnur; Hasanah, Kartini Dwi (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This study aims to find out how the influence of learning motivation on students of Islamic Religious Education subjects by using comic media for friends of Muslim children at SDN Gondang in grades V and grade VI. This research approach uses an experimental approach with a pretest-posttest control group design. In this design there is a pre-test, before being treated with comic media and a post-test after being given treatment with comic media. The test instrument used is multiple choice questions that have been tested for validity. The sample in this study was class V as the control class and class VI as the experimental class with a total population of 72 students. Muslim children's friend comics contain stories of good morals in everyday life which are packed with children's daily stories with various interesting pictures and stories. The results showed that there was an influence on students' learning motivation for the pretest experiment and posttest experiment after being given comic media for Muslim children's friends in class VI SDN Gondang on the subject of Islamic Religious Education. This is based on the results of hypothesis testing in the pretest of the experimental class and the posttest of the experimental class showing significant results obtained by the Sig value. (2-tailed) of 0.007 > 0.05. And the acquisition of tcount > ttable for the experimental class is 2.887 > 1.688, which means that H0 is rejected and Hа is accepted.